Pola Komunikasi Interpersonal Klub Futsal (Studi Deskriptif pada Tim Harapan FC) - Setiawan, Ari (Green Publisher Indonesia, 2024)
Futsal is a sport with fast and dynamic intensity that requires teamwork. Therefore, it requires direct and fast communication to understand movement through patterns and interpersonal communication that is useful for minimizing errors. This study uses a qualitative descriptive approach using data analysis in the form of observation, interviews and documentation. The purpose is to discuss the importance of interpersonal communication patterns between coaches and captains of the Harapan FC futsal team. When the interaction takes place, it produces responses and feedback, which is included in the communication pattern to achieve the goal of effective interperonal communication in the Harapan FC futsal team. In the communication pattern, there are various networks that are formed as a flow of communication between individuals, in addition to the effectiveness of interpersonal communication, there are Respect, Empathy, Audible, Clarity and Humble. The result of the research is that there is a concept of communication patterns and interpersonal communication in the training sessions. When the coach gives a message about the technique, the player follows the technique in the form of a wheel communication pattern, a Y communication pattern and a star communication pattern. The communication pattern is also to find out the attitude of Respect, directing the captain to help the player in improving Empathy. Then there is an evaluation session after the match, on this occasion Audible and Clarity can be found in the use of techniques that are carried out and then explained in the evaluation. So that the captain and players are able to know the meaning of techniques in training, if they are able to master the technique, the captain must remain humble and be able to introspect himself or other players to be able to improve the quality and skills of the players.